Appointment of Notaries under Indonesian and Singaporean Law: Pengangkatan Notaris dalam Hukum Indonesia dan Singapura - Widjaja, Viona; Djaja, Benny (Rechtsidee, 2025)
General Background: Notaries play a vital role in society by providing legal certainty through authentic deeds. Specific Background: However, their status and appointment processes vary significantly depending on the legal system of a country. Knowledge Gap: There is limited comparative analysis regarding the appointment of notaries in civil law countries like Indonesia and common law countries like Singapore. Aims: This study aims to analyze and compare the legal frameworks governing the appointment of notaries in Indonesia and Singapore, highlighting their differences, similarities, strengths, and weaknesses. Results: The findings reveal significant differences in the appointment process, requirements, and supervisory authority. In Indonesia, notaries are appointed by the Minister of Law and Human Rights based on Law No. 2 of 2014, while in Singapore, the appointment is conducted by the Senate of the Singapore Academy of Law under the Notaries Public Act Chapter 208. Novelty: This study offers a focused comparative analysis of notarial appointment processes within two distinct legal traditions—civil law and common law—which is rarely addressed in previous literature. Implications: The results provide practical insights for legal practitioners and policymakers in Indonesia and offer considerations for improving the notarial appointment system in line with global best practices. Highlights: Highlights the structural differences in notary appointments between Indonesia and Singapore. Reveals the impact of legal traditions (civil vs. common law) on notarial authority. Provides insights to improve Indonesia’s notarial appointment process. Keywords: Notary Appointment, Comparative Law, Civil Law, Common Law, Legal System